2008
DOI: 10.1002/bip.20788
|View full text |Cite
|
Sign up to set email alerts
|

Fasciola gigantica cathepsin L proteinase‐based synthetic peptide for immunodiagnosis and prevention of sheep fasciolosis

Abstract: ABSTRACT:Sheep fasciolosis is a devastating burden for the livestock industry. We herein report on immunodiagnosis of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…[75] Subsequently, the synthetic polypeptides that represented the full-length mature protein sTS14 were assessed for serologic potential using ELISA for the diagnosis of NCC. [76] Since then, pure epitopes and molecules are being increasingly used as diagnostic antigens in a large number of parasitic infections including malaria,[77] Chagas’ disease,[78] leishmaniasis,[79] schistosomiasis,[80] cystic echinococcosis,[81] fascioliasis,[82] and cysticercosis. [83]…”
Section: Antigens Of the Cysticercimentioning
confidence: 99%
“…[75] Subsequently, the synthetic polypeptides that represented the full-length mature protein sTS14 were assessed for serologic potential using ELISA for the diagnosis of NCC. [76] Since then, pure epitopes and molecules are being increasingly used as diagnostic antigens in a large number of parasitic infections including malaria,[77] Chagas’ disease,[78] leishmaniasis,[79] schistosomiasis,[80] cystic echinococcosis,[81] fascioliasis,[82] and cysticercosis. [83]…”
Section: Antigens Of the Cysticercimentioning
confidence: 99%
“…Despite such a large number of potential synthetic peptides having been identified, none are currently being marketed for human use [16] and few studies reported to date have used synthetic peptides as anti-helminth vaccines, including Echinococcus granulosus [17], Trichinella spiralis [18], Brugia malayi [19], Taenia solium [20], Schistosoma mansoni [21] and F. gigantica [22]. Regarding F. hepatica , synthetic peptides have been used in diagnosing human infections.…”
Section: Introductionmentioning
confidence: 99%
“…Quite a number of relatively cheap antibody detection indirect enzyme-linked immunosorbent assays (ELISA) with high sensitivity and specificity have been developed. Most of these techniques are based on excretory-secretory products and cathepsin L proteases [70,73].…”
Section: Diagnosis Of Fascioliasismentioning
confidence: 99%